Vietnam : 2022 Article IV Consultation-Press Release; Staff Report, and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2022)
Spurred by an impressive vaccination drive, the economy is rebounding from a severe pandemic wave. The government successfully maintained fiscal, external, and financial stability. Nonetheless, the labor market recovery is lagging, with sizeable underemployment, small and medium sized enterprises remain vulnerable, problem loans are rising, real estate and corporate bond market risks are elevated, and the pandemic exacerbated longstanding structural challenges.